Keefektifan Konseling Kelompok Cognitive Behavioral Therapy (CBT) dengan Teknik Cognitive Restructuring untuk Meningkatkan Self-Esteem pada Siswa - Risma Kumara Rani; Dwi Yuwono Puji Sugiharto; Sugiyo Sugiyo (Kuras Institute, 2022)
Self esteemis one of the most important needs for individuals to function effectively. Students who have low self esteemtend to have feelings of instability or insecurity, lack confidence, are more concerned with protecting themselves from painful things than actualizing opportunities. Therefore, this study tried to examine the effectiveness of group counseling with cognitive restructuring techniques to improve self-esteem. Furthermore, the method used was an experiment with the RandomIzed Design Of Pretest-Posttest Control Group involving 14 selected X-grade students in purposive sampling. Data collection using instruments from Tafarodi & Swan with Self-Liking / Self-Competence Scale. After their data was analyzed, it was found that counseling cbt groups with cognitive restructuring techniques was effective in improving self-esteem.